Temporal course of attention bias toward emotional faces in individuals with autistic traits: an eye-movement study - Meng, Chunyan; Li, Taolin; Wang, Jing (Frontiers in Neuroscience, 2023)
Introduction: Similar attention patterns have been found in individuals with autism spectrum disorder (ASD) and autistic traits (ATs). The Intense World Theory and previous studies suggest that individuals with ASD may demonstrate a vigilance-avoidance attention pattern towards emotional faces. However, the attention patterns in individuals with ATs remain unclear. Therefore, this study employed eye-tracking technology to examine the characteristics and temporal course of attention bias towards emotional faces in individuals with ATs.The Autism-spectrum Quotient (AQ) was used to evaluate the level of ATs among 2,502 college students. Fifty participants were selected from the 2,502 college students: the 25 high-AQ group participants were randomly selected from the 10% of individuals with the highest AQ scores.Similarly, the 25 low-AQ group participants were randomly selected from the 10% of participants with the lowest AQ scores. All selected participants completed an eye-tracking study while performing a dot-probe task with emotional faces (positive-neutral, negative-neutral, and negativepositive). By analyzing data from different time periods, the attention bias and time course of individuals with ATs towards emotional faces were investigated.The results showed that compared to the low-AQ group, the high-AQ group detected negative faces faster in the early stages of emotional face processing. As the presentation time of emotional faces increased (at the 2-3 s mark), the fixation scores for negative-neutral faces of the high-AQ group were less than 0.5, which was significantly lower than those of the low-AQ group.Meanwhile, the high-AQ group showed a brief attentional avoidance to positive emotion at 3-4 s in the positive-neutral trials, indicating that the high-AQ group exhibited attention avoidance to both negative and positive faces during the middle and later stages of emotional processing.This study suggests that individuals with ATs display a vigilance-avoidance pattern to emotional faces. It contributes to a deeper understanding of the mechanisms of attention in persons with ATs and further supports the Intense World Theory.